2014
DOI: 10.1080/19371918.2014.893854
|View full text |Cite
|
Sign up to set email alerts
|

Peer Navigators and Integrated Care to Address Ethnic Health Disparities of People with Serious Mental Illness

Abstract: People of color with serious mental illnesses experience high rates of morbidity and mortality. Patient navigators, developed for cancer care, may help this group benefit from integrated care. This review examined patient navigators’ key ingredients for cancer care for relevance to patients of color for application of peer services to psychiatric goals. Among cancer patients, navigators lead to greater treatment engagement and improved health outcomes for ethnic minority groups. Research also suggests peers ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 92 publications
(105 reference statements)
1
48
0
Order By: Relevance
“…14, 27 Hence, the CBPR team conducting the earlier qualitative study 12 used study results to adapt navigator guidelines for the needs and priorities of African Americans with serious mental illness who were homeless. 28 Here, we report findings from a subsequent RCT comparing the effectiveness of this peer navigator program (PNP) to treatment as usual (TAU). We expected to show people participating in PNP would report improvements in both psychiatric and physical health which would correspond with a better sense of recovery and improved quality of life.…”
mentioning
confidence: 99%
“…14, 27 Hence, the CBPR team conducting the earlier qualitative study 12 used study results to adapt navigator guidelines for the needs and priorities of African Americans with serious mental illness who were homeless. 28 Here, we report findings from a subsequent RCT comparing the effectiveness of this peer navigator program (PNP) to treatment as usual (TAU). We expected to show people participating in PNP would report improvements in both psychiatric and physical health which would correspond with a better sense of recovery and improved quality of life.…”
mentioning
confidence: 99%
“…Our study showed peer workers serve as co-facilitators, navigators and language interpreters. By helping to serve as an interface between patients and the treatment team, peer leaders contribute to patients’ greater treatment engagement and improved health outcomes [48]. Peer leaders also help to supplement the gaps in services where there is a lack of cultural competency and resources.…”
Section: Discussionmentioning
confidence: 99%
“…The next step is to use the information herein to develop a peer navigator program and evaluate its effectiveness on the health care needs of this population. The research literature has begun to yield suggestions about the outlines of these programs; 39, 40 one study shows a California version of peer navigators yielded significantly fewer reports of pain and health symptoms after six months compared to a control group. 41 Our CBPR team is combining these insights with findings from the qualitative research herein to develop a peer navigator program for people in Chicago’s Edgewater-Uptown neighborhood.…”
Section: Discussionmentioning
confidence: 99%